Vascular dysfunction in HFpEF: Potential role in the development, maintenance, and progression of the disease - Saavedra-Alvarez, Andrea; Pereyra, Katherine V. V.; Toledo, Camilo; Iturriaga, Rodrigo; Del Rio, Rodrigo (My University, 2022)
Heart failure with preserved ejection fraction (HFpEF) is a complex, heterogeneous disease characterized by autonomic imbalance, cardiac remodeling, and diastolic dysfunction. One feature that has recently been linked to the pathology is the presence of macrovascular and microvascular dysfunction. Indeed, vascular dysfunction directly affects the functionality of cardiomyocytes, leading to decreased dilatation capacity and increased cell rigidity, which are the outcomes of the progressive decline in myocardial function. The presence of an inflammatory condition in HFpEF produced by an increase in proinflammatory molecules and activation of immune cells (i.e., chronic low-grade inflammation) has been proposed to play a pivotal role in vascular remodeling and endothelial cell death, which may ultimately lead to increased arterial elastance, decreased myocardium perfusion, and decreased oxygen supply to the tissue. Despite this, the precise mechanism linking low-grade inflammation to vascular alterations in the setting of HFpEF is not completely known. However, the enhanced sympathetic vasomotor tone in HFpEF, which may result from inflammatory activation of the sympathetic nervous system, could contribute to orchestrate vascular dysfunction in the setting of HFpEF due to the exquisite sympathetic innervation of both the macro and microvasculature. Accordingly, the present brief review aims to discuss the main mechanisms that may be involved in the macro- and microvascular function impairment in HFpEF and the potential role of the sympathetic nervous system in vascular dysfunction.
Keywords: inflammation; oxidative stress; heart failure; vascular dysfunction; preserved ejection fraction heart failure (hfpef)